Analisis Sumber dan Penggunaan Modal Kerja Pada PT. Langgeng Makmur, Tbk - Anshar, M Chairul; Basri, Surya Kelana; Rezky, Endyta (Khazanah Journal: Economics, Muamalah & Entrepreneurship, 2023)
This research aims to determine the source and use of working capital at PT. Langgeng Makmur Industri, Tbk. 2021-2022. The type of data used is quantitative and qualitative data. The data source used is secondary data. The analytical method used is descriptive. The research results show that the source of working capital in 2021-2022 is IDR 27,188,732,886,- while the use of working capital is IDR 34,410,246,567,- with a decrease difference of IDR 7,221,513,681.- which is due to changes in working capital originating from the reduction assets, increase in each type of debt and capital that is not well realized, thus it can be concluded that the use of working capital is greater than the working capital sources owned by PT. Langgeng Makmur Industri, Tbk. 2021-2022.